Population Aging and International Health-Caregiver Migration to Japan - Vogt, Gabriele (SpringerBriefs in Population Studies,, 2018)
This book introduces Japan's current policy initiatives directed at eldercare and international labor migration, and, wherever appropriate,it adds a comparative perspective from Germany. The book shows how eldercare is currently being organized and discusses integration policies for foreigners. It studies the policy-making process behind the system, and contextualizes the migration avenue within the strong roots of Japan's eldercare in local communities and the non-preparedness of the nation to grant local citizenship to international newcomers. Through applying an approach of multi-level policy making, putting a strong focus on the local level and introducing new approaches, this book is of interest to policy makers and scholars in aging, migration, health care, and contemporary Japan.